Richardson-Sinkler connections : planting, politics, horses, and family life, 1769-1853 - Little, Harriet Clare Sinkler (The University of South Carolina Press, 2019)
"In 2008 Harriet Clare Sinkler Little, William Henry Sinkler, and Norman Sinkler Walsh donated their collection of Sinkler family documents to the South Caroliniana Library. Included were numerous letters written to their third great-grandfather, William Sinkler, the majority of them from his first cousin and brother-in-law, James Burchell Richardson. Encouraged by Dr. Allen Stokes, Harriet Little continued her transcription of these letters, while extending her search for William Sinkler's letters to James Burchell Richardson (thus far not found). Additional letters and other documents were located, some in other South Caroliniana Library collections, some at the Rubenstein Library at Duke University, and several at the South Carolina Historical Society"--